The Influence of Attitude on Farmers' Decision-Making Process in Using Certified Quality Seeds in Hilly Areas - Wulandari, Asih Sri; Kurniati, Dewi; Maswadi, Maswadi (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2024)
The use of certified quality seeds is critical to increasing agricultural productivity. However, its use still needs to be improved in Bengkayang Regency, especially in hilly areas that pose unique challenges to agricultural practices. This study analyzed the influence of farmers' attitudes on their decision to use certified quality seed in the region. The research method used a mixed approach, combining descriptive analysis to collect data through a comprehensive questionnaire from farmers who have and have not used certified quality seeds. The sample consisted of 111 farmers in the Bengkayang district, representing a wide range of farming backgrounds and experiences. Fishbein's multi-attribute analysis and structural equation modeling (SEM) were used for in-depth data analysis, which provided vital insights into the factors influencing farmers' decisions. The results showed that farmers positively evaluated several attributes of certified quality seed, indicating confidence in its reliability, yield potential, and relevance to local conditions. These positive attitudes are mainly driven by agricultural motivation, perceived economic benefits, and careful decision evaluation. It is important to note that effective, cognitive, and cognitive attitudes jointly influence farmers' decision-making in selecting certified quality seed, indicating the complexity of the adoption process involving emotional, rational, and behavioral aspects. The results of this study provide valuable information for rice farmers and policymakers at the government level to design effective strategies to increase the use of quality seeds. Recommendations are developing targeted extension programs, improving access to quality seeds, and implementing incentives to encourage wider adoption among farmers in Bengkayang Regency.